Astyanax hermosus, a new species from the Primero River basin, Córdoba, Argentina (Characiformes, Characidae) - Miquelarena, Amalia María (2005)
A new species of the characid genus Astyanax is described from the endorheic Primero River basin, in central Argentina: Astyanax hermosus sp. n. This species can be distinguished from all other in the genus by the following combination of characters: body relatively low (33.1-38.7% SL); head short (23.5-27.1% SL); snout short (18.3-26.6% HL); interorbital broad (34.9-41.5% HL); maxilla with 1-3 teeth, usually one; iv-v, 17-22 anal-fin rays; 35-38 perforated scales on the lateral line; transverse scales 7/6; and distinctive color pattern, with Y-shaped humeral spot, a broad grayish longitudinal stripe on the flanks, extending weakly onto the middle caudal-fin rays, and extremely dark opercular, subopercular and preopercular regions. In addition, the males of the new species are distinguished by the presence of bony hooks in all their fins.